2018
DOI: 10.1080/15412555.2018.1486396
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-Facilitated Physical Activity Intervention Versus Pulmonary Rehabilitation for Improving Physical Activity in COPD: A Feasibility Study

Abstract: Pulmonary rehabilitation (PR) may not suit all individuals with chronic obstructive pulmonary disease (COPD) and may not result in increased physical activity. Higher levels of physical activity are associated with reduced mortality and morbidity. The aim of this study was to assess the feasibility of conducting a trial to investigate the effectiveness of a clinician-facilitated physical activity intervention (PAI) versus PR in improving physical activity in patients with COPD referred to PR. In this randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Igualmente, los estudios muestran mejoría en la disnea, fuerza muscular y tolerancia al ejercicio en pacientes con EPOC leve; estos pacientes se benefician de ser incluidos rutinariamente en programas de rehabilitación pulmonar (33,34), lo cual tiene una asociación con la reducción significativa en la tasa de exacerbación, posterior al tratamiento recibido en el programa de rehabilitación pulmonar (35). Deepak,et al (36), afirman que la rehabilitación pulmonar temprana en EPOC tiene beneficios significativos en la calidad de vida y la mejoría en el ejercicio.…”
Section: Discussionunclassified
“…Igualmente, los estudios muestran mejoría en la disnea, fuerza muscular y tolerancia al ejercicio en pacientes con EPOC leve; estos pacientes se benefician de ser incluidos rutinariamente en programas de rehabilitación pulmonar (33,34), lo cual tiene una asociación con la reducción significativa en la tasa de exacerbación, posterior al tratamiento recibido en el programa de rehabilitación pulmonar (35). Deepak,et al (36), afirman que la rehabilitación pulmonar temprana en EPOC tiene beneficios significativos en la calidad de vida y la mejoría en el ejercicio.…”
Section: Discussionunclassified
“…18,30 Interventions occurred in-hospital (n = 1), 35 in an outpatient clinic (n = 3), [16][17][18] remotely (eg, via telephone) (n = 3), 19,29,38 or across multiple settings (combination of in-hospital or outpatient setting) and remote sessions via telephone, email, or text (n = 10). 21,22,28,[31][32][33][34]36,37,39 Intervention setting was not reported in 1 study. 30 Common themes were identified regarding content and design of physical activity counseling interventions.…”
Section: Characteristics Of Included Interventionsmentioning
confidence: 98%
“…[16][17][18][19]21,22,[28][29][30][31][33][34][35]39 Goal setting either through an algorithm (eg, based on previous week's physical activity level or step count) or through collaborative goal setting was employed in 15 studies. [16][17][18][19]21,22,[28][29][30][32][33][34]36,38,39 More than half of included studies (n = 10) used a system such as a diary or a smartphone app to record physical activity such as daily step counts or exercise. 16,18,21,22,29,[31][32][33][34]39 In the studies that included goal setting, common themes were identified.…”
Section: Characteristics Of Included Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a population study such as KORA, participants with higher lung function had more activity as measured by Actigraph hip accelerometers, but there were few COPD participants in this study 16. There are also efforts to integrate sensors in pulmonary rehabilitation research, such as a recent pilot study used an Actigraph CT3X+accelerometer to assess changes in steps after randomisation to pulmonary rehabilitation or a clinician-facilitated physical activity intervention 17…”
Section: Introductionmentioning
confidence: 99%